2018
DOI: 10.1016/j.btre.2018.e00275
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of bacteria isolated from Red Sea marine invertebrates

Abstract: HighlightsRevealing the biodiversity of Red Sea marine invertebrates associated microorganisms by 16S rRNA sequence analysis.Isolation of bacteria and actinomycetes with antimicrobial activity from different Red Sea invertebrates.Detection of biosynthetic gene clusters (PKS and NRPS) in microorganisms associated with the Red Sea marine invertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The presence of biosynthetic gene clusters (BGC) was screened to understand the ability of the prospective fungi to produce bioactive polyketides and non-ribosomal peptides. Some studies demonstrated that the presence of biosynthetic gene cluster (BGC) such as polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS) genes in microorganisms is correlated to their capability to inhibit the growth of other microorganisms (Passari et al 2016;Böhringer et al 2017;Samak et al 2018). We detected the existence of PKS-I, PKS-II and NRPS genes in Eutypella sp.…”
Section: Discussionmentioning
confidence: 91%
“…The presence of biosynthetic gene clusters (BGC) was screened to understand the ability of the prospective fungi to produce bioactive polyketides and non-ribosomal peptides. Some studies demonstrated that the presence of biosynthetic gene cluster (BGC) such as polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS) genes in microorganisms is correlated to their capability to inhibit the growth of other microorganisms (Passari et al 2016;Böhringer et al 2017;Samak et al 2018). We detected the existence of PKS-I, PKS-II and NRPS genes in Eutypella sp.…”
Section: Discussionmentioning
confidence: 91%
“…Type I PKS gene cluster detection was used Thermo Scientific 2X Phire Plant Direct PCR Master Mix with MDPQQR f (5'-RTRGAYCCNCAGCAIC G-3') and HGTGT r (5'-VGTNCCNGTGCCRTG-3') primer pair (El Samak et al, 2018). The PCR condition was 98°C for 5 min for initial denaturation; then 10 cycles consisting of a denaturation stage at 98°C for 5 sec, annealing stage at 60°C (temperature reduced 2°C per cycle) for 5 sec, extension stage at 72°C for 1 min, followed with 30 cycles with a denaturation stage at 98°C for 1 min, annealing stage at 40°C for 5 sec, extension stages at 72°C for 1 min, and a final extension stage at 72°C for 1 min and a cooling stage at 4°C.…”
Section: Nrps and Pks Gene Type II Cluster Amplificationmentioning
confidence: 99%
“…The PCR condition was 98°C for 5 min for initial denaturation; then 10 cycles consisting of a denaturation stage at 98°C for 5 sec, annealing stage at 60°C (temperature reduced 2°C per cycle) for 5 sec, extension stage at 72°C for 1 min, followed with 30 cycles with a denaturation stage at 98°C for 1 min, annealing stage at 40°C for 5 sec, extension stages at 72°C for 1 min, and a final extension stage at 72°C for 1 min and a cooling stage at 4°C. PKS-II gene amplification was carried out by mixing the primary pair of PF6 (5'-TSGCSTGCTTGG AYGCSATC-3 ') and PR6 (5'TGGAANCCGCCGAA BCCGCT-3') (El Samak et al, 2018), 1 µL each at a concentration of 10 mM, with 1 µL of extracted template DNA, 10 µL of Thermo Scientific2X Phire Plant Direct PCR Master Mix, and 8 µL of ddH2O. PCR amplification process was carried out in 40 cycles with the following stages: initial denaturation stage (98°C, 5 min), followed by denaturation (98°C, 5 sec), annealing (70°C, 5 sec), extension stage (72°C, 1 min), and the final extension (72°C, 1 min).…”
Section: Nrps and Pks Gene Type II Cluster Amplificationmentioning
confidence: 99%
“…Perhaps the hallmark of human benefit from a marine gene is the discovery of green fluorescent protein, which produces bioluminescence in the jellyfish Aequorea victoria and has been used across a range of applications from protein tagging to identifying levels of environmental toxicity, contributions ultimately recognized with the 2008 Nobel Prize in Chemistry 27 . Further examples include bioprospecting for novel antifoulants and adhesives, and the search for novel antibiotics, which has increasingly focused on the bioactive compounds produced by marine invertebrates and microorganisms associated with sea sponges [28][29][30] . Other marine microorganisms produce a type of naturally occurring polymer (extracellular polymeric substance) that is of interest in bioremediation efforts due to its capacity to detoxify pollutants such as heavy metals 31 , while Pseudomonas spp.…”
Section: Commercial Benefitsmentioning
confidence: 99%